Characteristics and risk profile of psoriasis patients included in the Czech national registry BIOREP and a comparison with other registries - Kojanova, Martina; Fialova, Jorga; Cetkovska, Petra; Gkalpakiotis, Spyridon; Jircikova, Jitka; Dolezal, Tomas; Arenberger, Petr; BIOREP study group (International journal of dermatology, 2017)
BACKGROUND: BIOREP is a Czech registry of psoriatic patients on biological treatment in a clinical setting. We describe the characteristics of patients with psoriasis at the time of enrollment and present comparisons with published data from other national registries. METHODS: We analyzed the cohort of patients treated with biologics between May 2005 and May 2015. Demographic data, previous therapies, comorbidities, and severity of psoriasis were compared with data from other registries - DERMBIO, BIOBADADERM, BADBIR, and PSOBEST. RESULTS: A total of 1412 psoriatic patients initiating biological treatment were included with a predominance of males (63.4%). The mean patient age was 50.2 years, and approximately 70.5% of patients were either overweight or obese. The mean baseline Psoriasis Area and Severity Index was 19.8, and the Dermatology Life Quality Index was 16.6. More than one-third of patients (41.0%) reported a history of psoriatic arthritis, and a high proportion of patients (49.5%) with cardiovascular risk factors (hypertension [35.2%], hyperlipidemia [27.7%], diabetes mellitus [11.4%], coronary heart disease [4.9%], and obesity [15.2%]) were observed. Most of the patients had been previously treated with phototherapy (85.4%), acitretin (74.0%), methotrexate (65.7%), or cyclosporine (53.1%). CONCLUSION: BIOREP is one of the first registries of patients with psoriasis treated with biologics in Central and Eastern Europe. Our results found a similar or higher prevalence of comorbidities, long disease duration, and high impact on the quality of life among patients included in Western European registries.
Keywords: obezita; Registries; Humans; index tělesné hmotnosti; methotrexát; lidé středního věku; Body Mass Index; Hypertension; registrace; Psoriasis; prevalence; Quality of Life; Female; rizikové faktory; dermatologické látky; dospělí; Methotrexate; psoriáza; Phototherapy; komorbidita; lidé; kvalita života; Retreatment; acitretin; Diabetes Mellitus; fototerapie; Adult; cyklosporin; ženské pohlaví; stupeň závažnosti nemoci; Comorbidity; Hyperlipidemias; Male; hypertenze; Middle Aged; Retrospective Studies; koronární nemoc; Coronary Disease; Czech Republic; Keratolytic Agents; Severity of Illness Index; Prevalence; biologické přípravky; hyperlipidemie; retrospektivní studie; Cyclosporine; Dermatologic Agents; Obesity; Česká republika; mužské pohlaví; Acitretin; diabetes mellitus; keratolytika; Biological Products; opakovaná terapie; Risk Factors